2020
DOI: 10.3389/fpsyg.2020.01297
|View full text |Cite
|
Sign up to set email alerts
|

Do 6-Month Motor Skills Have Cascading Effects on 12-Month Motor and Cognitive Development in Extremely Preterm and Full-Term Infants?

Abstract: In this study, we analyzed whether 6-month gross and fine motor skills were related to 12-month gross and fine motor skills and cognitive development, controlling for 6-month cognitive skills, and neonatal status (extremely low gestational age ELGA ≤ 28 weeks vs. full-term FT ≥ 37 weeks). We also investigated, at 6 months, predictive indexes for motor and cognitive delay at 12-months. We assessed 40 infants (20 ELGA and 20 FT) at 6 and 12 months (corrected age for the ELGA infants). Six-month gross motor skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Consistent associations of microbiota b-diversity with infant gut microbiota were observed for FM subscale in our study. FM abilities refer to the control of small muscles that is highly related to cognitive functions that process visual information [ 39 ]. Despite this connection, examination of Bayley ® -III scales showed no significant associations of cognitive and language subscales with gut microbiota in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent associations of microbiota b-diversity with infant gut microbiota were observed for FM subscale in our study. FM abilities refer to the control of small muscles that is highly related to cognitive functions that process visual information [ 39 ]. Despite this connection, examination of Bayley ® -III scales showed no significant associations of cognitive and language subscales with gut microbiota in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The cascading effects of early motor development on other developmental domains in preterm children have been highlighted in several studies (Zuccarini et al, 2020). Developmental changes in one domain can have cascading effects on others, even seemingly unrelated ones-they can be direct or indirect as well as multidirectional (Iverson, 2021(Iverson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies that used standardized assessment tools reported similar results at different ages. Gross motor skills assessed at 6 months by Griffiths Mental Developmental Scales were associated with cognitive skills at 12 months with the same instrument ( Zuccarini et al, 2020 ). The Prechtl General Movement Assessment (GMA) also was associated with cognitive outcomes assessed with different tools from 2 to 11 years old ( Einspieler et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations